Monitoring fire-fighters’ smoke exposure and related health effects during Gestosa experimental fires - Miranda, A. I. (2020)
The main objective of this study is to contribute to the scientific knowledge regarding fire-fighters’ exposure to smoke and its related health effects. Forest fire experiments were developed with an extensive number of measurements of individual exposure to smoke pollutants and of medical parameters for a group of fire-fighters. For the smoke exposure monitoring, ten fire-fighters from four different fire brigades were selected. The fire-fighters’ individual exposure to toxic gases and particulate matter was monitored with portable devices, and their location in time was registered with GPS equipment. For all the monitored fire-fighters, air pollutant concentration values acquired during the fire experiments were beyond the limits recommended by the World Health Organization (WHO), namely for PM2.5, CO and NO2. Daily averages of PM2.5 concentration values as high as 738 µg.m-3 were obtained, well above the recommended limit of 25 µg.m-3. In terms of CO, hourly averaged values higher than 73,000 µg.m-3 were monitored, clearly above the 30,000 µg.m-3 recommended by the WHO. The highest NO2 hourly averaged measured value was 4,571 µg.m-3, once again much higher than the recommended value of 200 µg.m-3. For VOCs, a maximum hourly average of 10,342 µg.m-3 was registered for one of the fire-fighters; however, due to the lack of recommended or legislated values it is not possible to establish a comparison. The medical tests conducted on the fire-fighters, before and after the exposure to smoke, also indicate a considerable effect on the measured medical parameters, in particular an expressive increase of CO concentration and a decrease of NO concentration in the exhaled air of the majority of the fire-fighters.